0875 Interrelations Among Race, Socioeconomic Status, Sleep Duration Variability, and Neurobehavior in Children with Obstructive Sleep Apnea Syndrome. (27th May 2020) - Williamson, A A; Fan, J; Xiao, R; Tapia, I E
Abstract: Introduction: There are racial and socioeconomic status disparities in child obstructive sleep apnea syndrome (OSAS) and in sleep patterns, but research on sleep patterns in children with OSAS is limited. This project examined interrelations among race, socioeconomic status (SES), sleep duration variability, and neurobehavior in children with OSAS. Methods: Baseline data were drawn from 464 children with OSAS (M age 7 years, SD 1.4 years; 49% male; 34% Black) participating in the Childhood Adenotonsillectomy Trial. Sleep duration variability was calculated as the coefficient of variation for 5-day sleep diaries. Linear regression was used to examine whether sleep duration variability was associated with child race (Black vs. non-black), SES (family income; maternal education; neighborhood distress index based on US Census data), z-scored body mass index, asthma, prematurity, and secondhand smoke exposure. We then examined whether sleep duration variability was associated with parent-and teacher-reported child neurobehavior including executive functioning (Behavior Rating Inventory of Executive Functioning) and inattention (Conners Rating Scale), adjusting for the variables included in the first regression analysis. Results: Black race was correlated with increased sleep duration variability (p = .05), but this association was not significant in the adjusted regression model. Secondhand smoke exposure was significantly associated with sleep duration variability (p<.001). Greater sleep duration variability was significantly associated with increased parent-reported neurobehavioral impairments (p=.004 for executive functioning and for inattention), adjusting for race, SES, secondhand smoke exposure, and the other covariates. Sleep duration variability was not associated with teacher-rated child neurobehavior. Conclusion: In children with OSAS, sleep duration variability is greater in those exposed to secondhand smoke and is linked to increased parent-rated child neurobehavioral impairments. Findings suggest that clinicians should screen for secondhand smoke exposure and that treatment of pediatric OSAS should include a focus on promoting healthy sleep patterns. Support: Sleep Research Society Foundation and K23HD094905 (AAW).